E-LEARNING IN PEDAGOGICAL STAFF TRAINING - Boris N. Kireev (Высшее образование в России)
The article focuses on the problems and prospects of implementing e-learning tools in training of future teachers. One of the ways to improve the effectiveness of training of students is to use blended learning, which combines multimedia learning and traditional tutoring with an emphasis on laboratory activities, the use of an interdisciplinary approach and e-learning. The mentioned approach facilitates obtaining competence and skills for organization of interactive educational process in schools and technical colleges. The ability to create, edit, share with multimedia objects of different types by using modern computer technologies will produce a beneficial effect on the formation of competence in multimedia communication.